2021
DOI: 10.3389/fpsyg.2021.730636
|View full text |Cite
|
Sign up to set email alerts
|

How Do Anchors' Characteristics Influence Consumers' Behavioural Intention in Livestream Shopping? A Moderated Chain-Mediation Explanatory Model

Abstract: Livestream shopping has become the focus of current marketing practises, while theoretical research on it is still in initial stages. Thus, from the para-social interaction (PSI) theory perspective, this study draws on cognitive–affective system theory as an analytical framework to explore internal mechanisms of how anchors' characteristics influence consumer behavioural intentions in livestream shopping while considering the characteristics of consumer online interaction propensity. We conducted a survey ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Thus, consumers may obtain limited hedonic and experiential value from the interaction with branded broadcasters (Lin et al, 2021). Meanwhile, celebrity broadcasters generally have an attractive appearance and character, which may bring joyful and exciting experiences to consumers (Hou et al, 2019;Zhu et al, 2021). Despite having less product knowledge and brand awareness than branded broadcasters, celebrity broadcasters also undergo preparations to be able to answer basic questions from consumers and arrange promotion activities .…”
Section: The Influence Of Broadcaster On Consumers' Intention To Foll...mentioning
confidence: 99%
“…Thus, consumers may obtain limited hedonic and experiential value from the interaction with branded broadcasters (Lin et al, 2021). Meanwhile, celebrity broadcasters generally have an attractive appearance and character, which may bring joyful and exciting experiences to consumers (Hou et al, 2019;Zhu et al, 2021). Despite having less product knowledge and brand awareness than branded broadcasters, celebrity broadcasters also undergo preparations to be able to answer basic questions from consumers and arrange promotion activities .…”
Section: The Influence Of Broadcaster On Consumers' Intention To Foll...mentioning
confidence: 99%
“…E-commerce anchors are the core of marketing strategy in livestreaming retailing. An e-commerce anchor is one who introduces and displays products comprehensively to customers ( Zhu et al, 2021 ). Unlike traditional television broadcasters, e-commerce anchors provide guidance to customers by sharing experiences based on their own consumption of the promoted products, answer viewers’ questions in real time, and interact with viewers based on their requests, and display products in ways that static images and texts cannot ( Sun et al, 2019 ; Han and Xu, 2020 ).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Unlike traditional television broadcasters, e-commerce anchors provide guidance to customers by sharing experiences based on their own consumption of the promoted products, answer viewers’ questions in real time, and interact with viewers based on their requests, and display products in ways that static images and texts cannot ( Sun et al, 2019 ; Han and Xu, 2020 ). Research has shown that the attributes, features, or characteristics of e-commerce anchors significantly influence purchase decisions or impulsive purchase on livestream shopping platform ( Li, 2021 ; Zhao and Feng, 2021 ; Zhu et al, 2021 ). Zhu et al (2021) classify anchors’ characteristics into physical attractiveness, professional ability, and social attractiveness.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Park and Lin (2020) identify that consumer potential behavior is impacted by the characteristics of celebrity-streamers. Zhu et al (2021), drawing on cognitive-affective system theory, uncover the influence of streamers' characteristics on consumer purchase intentions in livestream shopping. Moreover, Sun et al (2021) further suggest that consumer purchase intention is influenced by the interactivity of Internet celebrities.…”
Section: Literature Reviewmentioning
confidence: 99%